2005
DOI: 10.1172/jci24543
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1 regulates cellular transformation and metastatic behavior in colon cancer

Abstract: Disruption of the cell-cell junction with concomitant changes in the expression of junctional proteins is a hallmark of cancer cell invasion and metastasis. The role of adherent junction proteins has been studied extensively in cancer, but the roles of tight junction (TJ) proteins are less well understood. Claudins are recently identified members of the tetraspanin family of proteins, which are integral to the structure and function of TJs. Recent studies show changes in expression/cellular localization of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

53
540
4
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(601 citation statements)
references
References 47 publications
53
540
4
4
Order By: Relevance
“…In breast cancer, decreased expression of claudin-1 and -7 was reported 41 , but increased claudin-1 and -4 expression in the basal-like subtype 42 and increased claudin-4 expressin in poor prognosis and high tumor grade 43 were also published. In colon cancer, while decreased expression of claudin-1 was reported to be associated with higher tumor grade 44 , an opposite conclusion has also been reported 45 In the present study, we found that claudin-1 is a direct target of RUNX3. The latter is deeply involved in the TGF--signaling pathway, which is well related to gastric carcinogenesis.…”
Section: Discussioncontrasting
confidence: 53%
“…In breast cancer, decreased expression of claudin-1 and -7 was reported 41 , but increased claudin-1 and -4 expression in the basal-like subtype 42 and increased claudin-4 expressin in poor prognosis and high tumor grade 43 were also published. In colon cancer, while decreased expression of claudin-1 was reported to be associated with higher tumor grade 44 , an opposite conclusion has also been reported 45 In the present study, we found that claudin-1 is a direct target of RUNX3. The latter is deeply involved in the TGF--signaling pathway, which is well related to gastric carcinogenesis.…”
Section: Discussioncontrasting
confidence: 53%
“…Why this loss of nuclear claudin-1 occurs in the more metastatic stages of melanoma is unclear, but may indicate an association between claudin-1 sublocalization and metastatic potential. The absence of nuclear staining in the epidermis, and in metastases leads us to believe that this nuclear staining is not an artifact, and indeed not only claudin-1 (Dhawan et al, 2005), but other TJ proteins show a similar propensity. ZO-2, for example, can inhibit AP-1 and C/EBP transcription factors upon its entry into the nuclei of proliferating cells (Betanzos et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…The first is an extensive study of claudin-1 expression in colon cancer (Dhawan et al, 2005), which found that claudin-1 was aberrantly expressed both in the cytoplasm and in the nucleus, as demonstrated not only by Claudin-1 expression in melanoma PD Leotlela et al immunohistochemistry and immunofluorescence, but also by Western analysis of nuclear and cytoplasmic fractions. The second study was conducted in oral squamous carcinoma (OSC) cells, and found that claudin-1 overexpression enhanced the invasion of OSC cells via increases in MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…27 Here we showed that CLDN-1 expression is high in lung squamous cell carcinomas (both by protein detection and transcript quantification), but reduced or undetected in adenocarcinomas. Interestingly, an increase in CLDN-1 expression was observed in keratinized regions of squamous cell carcinoma of the epidermis, 14 and in colon cancers, 28 whereas a decrease or loss of expression was reported in breast cancer cell lines 29,30 and tumors. 31 These findings suggest that a squamous cell tumor phenotype is more likely to be correlated with high Tight junction proteins in human lung carcinomas S Paschoud et al CLDN-1 expression, whereas tumors with glandular components are more likely to lose CLDN-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our observation that in normal bronchial epithelium CLDN-1 is abundant in basal cells, but scarce or absent in cylindrical cells and pneumocytes raises the hypothesis that squamous cell carcinomas arise either from uncontrolled proliferation and lack of normal differentiation of the basal cells of the bronchial epithelium or from the reversion of differentiated cells to this phenotype. As CLDN-1 has been implicated in epithelial-mesenchymal transition, possibly through the modulation of the b-catenin/Tcf signaling pathway, 28 it is possible that CLDN-1 dysregulation may be part of the molecular pathway that leads to the development of squamous cell carcinomas. The pattern of CLDN-5 expression in normal bronchial epithelium and in tumors was essentially opposite to that of CLDN-1, with high expression in normal cylindrical cells, pneumocytes and adenocarcinomas, and low or undetectable expression in basal cells and squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%